Differences in perceived readiness to train between two menstrual cycle phases in female athletes - Noah Reinertz; Brett Crossland (Journal of Coaching and Sports Science, 2026)
Background: The menstrual cycle and associated physical symptoms, such as fatigue, mood swings, cramps, changes in energy levels, and physical discomfort, may directly influence athletic performance. Aims: The purpose of this study was to determine the effects of two stages of the menstrual cycle (early follicular & luteal phases) on recovery from exercise, as measured by heart rate variability, jumping performance, and a psychological wellness questionnaire in conjunction with current training regimes. Methods: A repeated measurement design was utilized, and statistical significance was set a priori at p < 0.05. Fifteen (n = 15) female participants (mean ± SD) for age, height, weight, body composition of 19.60 ± 1.3 years, 164.67 ± 5.78 cm, 62.44 ± 10.95 kg, and body composition 24.34 ± 6.45%), were tested in the early follicular and early luteal phase of their menstrual cycle. Results: Researchers observed significant differences in perceived readiness to train between the two phases. The early luteal phase showed a significantly higher (p < 0.01) score on the wellness questionnaire than the early follicular phase. No significant differences were found for HRV (p = 0.62), reactive strength index (p = 0.59), and vertical jump performance (p = 0.12) between the two phases. Conclusion: These results suggest that in the early luteal phase, athletes are less negatively affected by psychological factors and appear better prepared to train. However, these factors do not have a significant impact on performance metrics.